Empire Bridal Fantasy / Dayang Hafsah Abdul Naim ... [et al.] - Abdul Naim, Dayang Hafsah; Kassim, Norafzan; Ismail, Nuur Fasihah Afiqah; Alfred Nadus, Rachel Cheryll; Samry, Syariezhan (2010)
Empire Bridal Fantasy is a business that focusing on wedding services. The members of Empire Bridal Fantasy are Syariezhan Samry, Dayang Hassah Abdul Nairn, Nuurfasihah Afiqah Ismail, Rachel Cheryll Alfred Nadus and also Norafzan Kassim. We want to thank God for giving us strength in finishing this business proposal. After all the challenges that we had faced, this business proposal is finally make it to reality. This will not be happening if there is no cooperation among the entire group member. Goat Buddy Enterprise is a business that focusing on wedding services. Our official and shop building is located in Wawasan Plaza Kota Kinabalu, Sabah. Nowadays, day by day as we can see wedding services demanding are seriously increase in Malaysia especially around Sabah so that we take this advantages to build our business. Realize or no, it's a matter for whoever who want to make a wedding ceremony. Again, everyone is having their own dream in order to make a wonderful yet amazing marriage ceremony for once in a life times. In this matter, we hope that our business in wedding services can fulfill the dream of whoever will get marriage sooner. We also hope that our business will be a successful business so that it can inspire more wedding services to expand their business.